A cross- sectional study of refugees in Norway and Serbia: Levels of mental distress and social-demographic risk factors - Halldis Niesser Grøtvedt; Sverre Varvin; Ivana Vladisavljević; Bojana Trivuncic; Idunn Brekke (Elsevier, 2024)
This cross-sectional study has assessed and compared symptoms of anxiety, depression, and posttraumatic stress disorder (PTSD) among one refugee group during flight (in Serbia) and another refugee group after flight (in Norway). Results indicate high levels of mental distress in both samples of refugees (Serbia: N = 100, Norway: N = 78). Participants in Serbia reported higher levels of symptoms than the participants in Norway. Moreover, the study found that female gender, low education, refused asylum, high age, and concerns about family correlated with mental distress among the participants.